Methodology of formation of econometric competences of students in theoretical and practical classes of econometrics. - Ravshanova Khurshida Makhmanazarovna (Genius Publishing Group, 2024)
This article contains comments by the author about the method of formation of econometric competences of students in theoretical and practical classes of econometrics. Also, the three main classes in which econometric models can be used in analysis and forecasting, as well as the stages of the modular teaching system in teaching econometrics are presented.
Keywords: Econometric Model; Pair Regression And Correlation; Multiple Regression And Correlation